PERENCANAAN DAN PENERAPAN METODE E-COMMERCE BARU UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM KOTA SERANG BANTEN - Harsono, Pramudi; Tabroni, Tabroni; Bahits, Abdul; Romli, Ombi (Yayasan Education and Social Center, 2024)
The aim of this research is to determine the impact of planning and implementing new E-commerce methods on micro, small and medium businesses (MSMEs) in Serang, Banten. In the digital era, MSMEs must adopt online marketing strategies to remain competitive. This research uses surveys and data analysis from MSME owners in Serang City who have implemented online marketing technology. The variables examined include the type of online marketing innovation used, the level of adoption, and its effect on increasing sales. This research aims to provide an in-depth understanding of the contribution of online marketing to the economic growth of MSMEs in the region through collecting data from MSME respondents. Data analysis will identify relationships between the variables investigated, with the hope of providing insight to MSME owners, local governments and other stakeholders about the importance of using online marketing innovation as a strategy to increase MSME sales in Serang, Banten. In addition, it is hoped that this study will become a reference for other researchers who want to explore the potential of online marketing in supporting the growth of MSMEs in various locations